Solid papillary breast carcinomas resembling the tall cell variant of papillary thyroid neoplasms (solid papillary carcinomas with reverse polarity) harbour recurrent mutations affecting IDH2 and PIK3CA: a validation cohort. Issue 2 (1st June 2018) - Lozada, John R; Basili, Thais; Pareja, Fresia; Alemar, Barbara; Paula, Arnaud Da Cruz; Gularte‐Merida, Rodrigo; Giri, Dilip D; Querzoli, Patricia; Cserni, Gabor; Rakha, Emad A; Foschini, Maria P; Reis‐Filho, Jorge S; et al.
Abstract : Aims: Solid papillary breast carcinoma resembling the tall cell variant of papillary thyroid neoplasms (BPTC), also known as solid papillary carcinoma with reverse polarity, is a rare histological type of breast cancer that resembles morphologically the tall cell variant of papillary thyroid carcinoma. BPTCs are characterised by IDH2 R172 hotspot somatic mutations or mutually exclusive TET2 somatic mutations, concurrently with mutations affecting PI3K pathway‐related genes. We sought to characterise their histology and investigate the frequency of IDH2 and PIK3CA mutations in an independent cohort of BPTCs, as well as in conventional solid papillary carcinomas (SPCs). Methods and results: Six BPTCs, not previously analysed molecularly, and 10 SPCs were reviewed centrally. Tumour DNA was extracted from microdissected histological sections and subjected to Sanger sequencing of the IDH2 R172 hotspot locus and exons 9 and 20 of PIK3CA . All six BPTCs were characterised by solid, papillary and follicular architecture with circumscribed, invasive tumour nodules composed of epithelial cells with reverse polarity. IDH2 mutations were identified in all six BPTCs (three R172S, two R172T and one R172G), four of which also harboured PIK3CA mutations (two H1047R, one Q546K and one Q546R). By contrast, all SPCs lacked IDH2 mutations, while one of 10 harboured a PIK3CA mutation (H1047R). Conclusion: We validated the presence of IDH2 R172 hotspot mutations and PIK3CA hotspot mutations in 100% and 67% BPTCs tested, respectively, and documented absence of IDH2 R172 mutations in SPCs. These findings confirm the genotypical–phenotypical correlation reported previously in BPTC, which constitutes an entity distinct from conventional SPC.